Establishing a learning agenda for learning health system implementation and research in Canada - Carly Whitmore; Marissa Bird; Shelley Vanderhout (PLoS ONE, 2025)
Health systems in Canada struggle to generate and use knowledge to improve equity-centred quadruple aim measures, resulting in care that is misaligned with local contexts. Learning Health Systems (LHS) offer a solution by aligning real-time evidence, informatics, patient-provider partnerships, and institutional strategies to support continuous improvements in care. Despite their potential, LHS initiatives in Canada remain siloed and lack harmonized leadership, knowledge exchange, and capacity building. To address these gaps, the Learning Health Hub was established to foster collaboration, disseminate best practices, and enhance collective capacity for LHS in Canada. In June 2024, the Learning Health Hub hosted its inaugural virtual symposium. This event brought together partners, researchers, health professionals, system operators, and policymakers from across Canada interested in LHS work. The symposium aimed to map assets and build momentum for larger-scale impact in LHS. Participants engaged in generative activities to define challenges and co-create solutions, resulting in the identification of key learning priorities. Three learning themes were identified: Patient, Caregiver, and Community Partnership; Enabling Environments; and Benchmarking and Evaluation. By advancing these themes, the Learning Health Hub aims to drive meaningful, sustainable change and improve healthcare quality and outcomes.